Preparation and application of nanosilver / carbon film / carbon fiber

By preparing nanosilver/carbon film/carbon fiber electrodes, using mesoporous materials and plasma processing technology, the problem of insufficient anti-interference ability of electrochemical sensors in complex samples is solved, achieving higher detection sensitivity and accuracy, and is suitable for the detection of a variety of environmental and biological samples.

CN114184655BActive Publication Date: 2025-02-28YANBIAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111359412.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-17
Publication Date
2025-02-28
Estimated Expiration
2041-11-17

AI Technical Summary

Technical Problem

In complex matrix samples, electrochemical sensors are susceptible to interference from electroactive coexisting components, resulting in hindering electron transfer between the analyte and the electrode, thereby reducing the accuracy, sensitivity and reproducibility of detection.

Method used

By preparing nanosilver/carbon film/carbon fiber electrodes, using mesoporous material coating and plasma treatment technology, the mechanical stability and biocompatibility of the electrode are improved, and nitrogen-doped carbon films and deposition of graphene quantum dots are prepared by electrode deposition method to enhance the catalytic activity and specific surface area of ​​the electrode.

Benefits of technology

It improves the anti-interference and anti-smudge capability of electrochemical sensors, enhances the detection sensitivity and accuracy of complex samples, reduces the lower detection limit, and expands the detection range, suitable for the detection of environmental pollutants and small biological molecules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114184655B_ABST
    Figure CN114184655B_ABST
Patent Text Reader

Abstract

The invention discloses a mesoporous material coated carbon fiber, which is prepared by the following method: 1) plasma treatment of carbon fiber electrode; 2) mesoporous material coating; nano silver / carbon film / carbon fiber, wherein the mesoporous material coated carbon fiber is used as a positive electrode, a polypyrrole film is prepared by an electrodeposition method, and carbonization; silver nitrate is added to a 0.1M KNO3 electrolyte to prepare nano silver / nitrogen doped carbon film / carbon fiber; the prepared nano silver / nitrogen doped carbon film / carbon fiber is used as a working electrode, Ag / AgCl is used as a reference electrode, and Pt is used as a counter electrode, a graphene quantum dot water dispersion solution is added to a buffer solution, and graphene quantum dots are deposited on the surface of the material; nano silver / graphene quantum dot / carbon fiber is used as a working electrode, silver nitrate is added to prepare nano silver / carbon film / carbon fiber; the prepared carbon fiber electrode improves the detection range and sensitivity, and reduces the detection lower limit; and can be widely used in electrochemical detection of various substances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of novel material preparation, and specifically relates to the preparation and application of nano silver / carbon film / carbon fiber. Background Art

[0002] In recent years, electrochemical sensors have developed into a mature technology with increasingly higher detection sensitivity. They have the advantages of good selectivity, simple operation, low cost, and easy connection with computers, and are often used in the detection of trace targets. Compared with technologies such as gas chromatography-mass spectrometry, liquid chromatography-mass spectrometry, and fluorescence detection, electrochemical sensors can respond to signals quickly while reducing the time for sample pretreatment. However, in the electrochemical analysis of complex matrix samples such as food, blood samples, and environmental samples, some electroactive coexisting components will produce interference signals. The above-mentioned contamination and interference will hinder the electron transfer between the analyte and the electrode, resulting in low accuracy, sensitivity, and reproducibility. Therefore, it is key to improve the anti-interference and anti-contamination capabilities of electrochemical sensors and realize the direct determination of targets in complex samples without sample pretreatment. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation method and application of nano silver / carbon film / carbon fiber in order to improve the anti-interference and anti-fouling capabilities of electrochemical sensors.

[0004] Mesoporous material coated carbon fiber, which is prepared by the following method:

[0005] 1) Plasma treatment of carbon fiber electrode: Tow carbon fiber is used as the base material, calcined at 400-500°C for 0.5-2h; rinsed with acetone, ethanol and deionized water for 3-5 times in sequence, and dried naturally; the treated carbon fiber is laid flat on a quartz boat, and plasma is evenly bombarded on the surface of the carbon fiber; the plasma power is 50-100W, the oxygen flow rate is 120-180mL / min, and the treatment time is 15-90s;

[0006] 2) Mesoporous material coating: immerse the carbon fiber treated in step 1) in the mesoporous material for 10 to 15 hours; soak under ultrasound for 3 to 10 minutes, take out, and calcine for 2.5 to 3.5 hours to obtain mesoporous material coated carbon fiber;

[0007] The mesoporous material is prepared by the following method: weigh 0.2-0.4 g P123, add 12-14 ml ethanol, 30-40 μl 1M hydrochloric acid, 1-2 ml water and 2-3 ml tetraethyl silicate, and rotate at a speed of 350-450 rpm at room temperature for 10-15 hours;

[0008] The P123 is 0.298 g, ethanol is 12.4608 ml, 1M hydrochloric acid is 33.34 μl, H2O is 1.6848 ml, and tetraethyl silicate is 2.2329 ml;

[0009] The tow carbon fiber has 3000 carbon fibers per tow.

[0010] Nanosilver / carbon film / carbon fiber, which is prepared by the following method:

[0011] 1) Preparation of nitrogen-doped carbon film / carbon fiber: adding 0.1M KNO3 and pyrrole monomer, taking the mesoporous material coated carbon fiber as the positive electrode, Pt as the negative electrode, and preparing polypyrrole film by electrodeposition under the conditions of 0.1g-2g pyrrole mass, 1-7V voltage, and 30-300s; placing in a corundum boat and carbonizing at a carbonization temperature of 400-900℃;

[0012] 2) Preparation of nanosilver / nitrogen-doped carbon film / carbon fiber: The nitrogen-doped carbon film / carbon fiber prepared in step 1) was used as a working electrode, and silver nitrate was added to a 0.1M KNO3 electrolyte. The cyclic voltammetry method was used to scan 5-15 cycles at -0.8~1V and a scan rate of 25mV / s to obtain nanosilver / nitrogen-doped carbon film / carbon fiber;

[0013] 3) Preparation of nanosilver / graphene quantum dots / carbon fiber: A standard three-electrode system is formed by using the nanosilver / nitrogen-doped carbon film / carbon fiber prepared in step 2) as the working electrode, Ag / AgCl as the reference electrode, and Pt as the counter electrode. A graphene quantum dot aqueous dispersion solution is added to a 0.01 M PBS buffer solution at pH = 7.4. Graphene quantum dots are deposited on the surface of the material by scanning 5-15 cycles at -2~2 V and a scan rate of 25 mV / s by cyclic voltammetry;

[0014] 4) Preparation of nanosilver / carbon film / carbon fiber: Using nanosilver / graphene quantum dots / carbon fiber as working electrodes, silver nitrate was added to 0.1M KNO3 electrolyte, and cyclic voltammetry was performed at -0.8~1V and a scan rate of 25mV / s for 5-15 cycles to obtain nanosilver / carbon film / carbon fiber;

[0015] The graphene quantum dot water dispersion solution has a concentration of 0.025-0.2 mg / ml.

[0016] Application of the nanosilver / carbon film / carbon fiber in the preparation of electrochemical sensors;

[0017] The nano silver / carbon film / carbon fiber is a working electrode.

[0018] The invention provides a mesoporous material coated carbon fiber, which is prepared by the following method: 1) plasma treatment of carbon fiber electrode: tow carbon fiber is used as base material, calcined at 400-500°C for 0.5-2h; acetone, ethanol and deionized water are used for sequential rinsing for 3-5 times, and the carbon fiber is naturally dried; the treated carbon fiber is laid flat on a quartz boat, and plasma is evenly bombarded on the surface of the carbon fiber; the plasma power is 50-100W, the oxygen flow rate is 120-180mL / min, and the treatment time is 15-90s; 2) mesoporous material coating: the carbon fiber treated in step 1) is immersed in the mesoporous material for 10-15h; the carbon fiber is immersed for 3-10min under ultrasonic action, taken out, and calcined for 2.5-3.5h to obtain the mesoporous material coated carbon fiber; nano silver / carbon film / carbon fiber is prepared by using the mesoporous material coated carbon fiber as a positive electrode, preparing a polypyrrole film by electrodeposition, and carbonizing; at 0.1M Silver nitrate was added to a KNO3 electrolyte, and cyclic voltammetry was used to scan 5-15 circles at -0.8~1V and a scanning rate of 25mV / s to prepare nanosilver / nitrogen-doped carbon film / carbon fiber; the prepared nanosilver / nitrogen-doped carbon film / carbon fiber was used as a working electrode, Ag / AgCl was used as a reference electrode, and Pt was used as a counter electrode, and a graphene quantum dot aqueous dispersion solution was added to a buffer solution, and cyclic voltammetry was used to scan 5-15 circles at -2~2V and a scanning rate of 25mV / s to deposit graphene quantum dots on the surface of the material; silver nitrate was added to a 0.1M KNO3 electrolyte, and cyclic voltammetry was used to scan 5-15 circles at -0.8~1V and a scanning rate of 25mV / s to prepare nanosilver / carbon film / carbon fiber;

[0019] The invention has the beneficial effects of: using the electrodeposition method to prepare a variety of carbon fiber electrodes loaded with silver nanoparticles on carbon films, carbon fiber as a base material has strong mechanical stability, conductivity and biocompatibility. After the polypyrrole film is carbonized, a dense nitrogen-doped carbon film is formed, providing a more polarized surface to ensure the good wettability of the carbon surface. At the same time, the modified graphene quantum dots provide sufficient active sites for the nucleation of Ag and improve their nucleation rate, and the graphene quantum dots have a large specific surface area and a control effect on the size, and the quantum confinement and edge effect of Ag help to form high-density ultrafine silver nanoparticles on the graphene quantum dots, further changing the electrode surface structure and increasing the catalytic active sites. The carbon fiber electrode of the present invention improves the detection range and sensitivity and reduces the detection limit. The electrode is widely used and can be used for the electrochemical detection of environmental pollutants such as dihydroxyphenol, nitrophenol, tetracycline, etc., and can also be used for the detection of biological small molecules such as dopamine, ascorbic acid, uric acid, etc. The preparation process of electrochemical sensors is simple and low-cost, and they have important application prospects in the simultaneous detection of phenolic isomers. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Scanning electron microscope image of the plasma-treated carbon fiber prepared in Example 1 of the present invention;

[0021] Figure 2 Scanning electron microscope image of the nitrogen-doped carbon film / carbon fiber prepared in Example 3 of the present invention;

[0022] Figure 3 Ip-pH relationship curves for detecting phenolic substances in different pH buffer solutions in Example 3 of the present invention;

[0023] Figure 4 Scanning electron microscope image of nanosilver / graphene quantum dots / carbon fiber prepared in Example 4 of the present invention;

[0024] Figure 5 CV graphs of hydroquinone and catechol detected at different scanning rates in Example 4 of the present invention;

[0025] Figure 6 DPV diagram and Ip-c relationship curve for detecting p-nitrophenol in the range of 1-200 μM in Example 5 of the present invention. DETAILED DESCRIPTION

[0026] Example 1 Preparation of plasma treated carbon fiber electrodes

[0027] 1. Preparation method

[0028] Take 3000 carbon fibers per bundle as the base material, put them into a muffle furnace and calcine them at 450℃ for 0.5-2h, then take them out, rinse them with acetone, ethanol and deionized water for 3-5 times in sequence, dry them naturally, and spread them evenly and dry them. Spread the treated carbon fibers flat on a quartz boat so that the high-speed ions in the plasma chamber can evenly bombard the surface of the carbon fibers, graft a sufficient amount of oxygen-containing functional groups on the surface of the carbon fibers, and increase the active sites on the surface of the electrode materials. Set the plasma power to 50-100W, the oxygen flow rate to 150mL / min, and the treatment time to 15-90s.

[0029] 2. Detection of phenolic substances

[0030] The plasma-treated carbon fiber was clamped with a platinum electrode clamp as the working electrode, Pt as the counter electrode, and Ag / AgCl electrode as the reference electrode. Cyclic voltammetry was performed in a 0.1M, pH=7.2 phosphate buffer solution (PBS) for 10 cycles until the electrode was stable. A certain amount of hydroquinone and catechol was added to the PBS solution, and the target was detected by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The potential window was -0.2-0.6V and the scan rate was 25mV / s. The specific parameters of the DPV test were: potential increment of 5mV, pulse amplitude of 50mV, pulse width of 50ms, and pulse period of 100ms.

[0031] result: Figure 1 The figure shows the morphology of carbon fiber after 40s of plasma treatment. The overall appearance is the same as the original morphology of carbon fiber, and the surface of the material is full of grooves. This proves that the oxygen plasma treatment only acts on the microscopic surface functional groups of the material, and the short-term oxygen ion bombardment will hardly cause damage to the surface morphology of the material.

[0032] Example 2 Construction of mesoporous material coated carbon fiber

[0033] Preparation of mesoporous material: 0.298 g P123 was weighed according to the ratio, 12.4608 ml ethanol, 33.34 μl 1 M hydrochloric acid, 1.6848 ml H2O and 2.2329 ml TEOS were added, and the mixture was rotated at 400 rpm at room temperature for 12 h.

[0034] The treated carbon fiber of Example 1 was immersed in the prepared mesoporous material for 12 hours and taken out after being immersed under ultrasound for 5 minutes. It was then calcined in a muffle furnace for 3 hours to form a mesoporous film on the surface of the carbon fiber, which greatly increased the specific surface area of ​​the carbon fiber.

[0035] Example 3 Preparation of Nanosilver / Nitrogen-doped Carbon Film / Carbon Fiber

[0036] 1. Preparation method

[0037] The plasma-treated carbon fiber and the mesoporous material-coated carbon fiber prepared in Example 1 and Example 2 were used as working electrodes, respectively, and polypyrrole film was prepared by electrodeposition. The electrolyte selected 0.1M KNO3, a certain mass of pyrrole monomer was added, and the pyrrole mass (0.1g-2g), voltage range (1V-7V), and time range (30s-300s) were regulated. The carbon fiber deposited with polypyrrole was placed in a corundum boat and carbonized in a tube furnace. The carbonization temperature range was (400°C-900°C) to obtain nitrogen-doped carbon film / carbon fiber. Using nitrogen-doped carbon film / carbon fiber as the working electrode, a certain amount of silver nitrate was added to the 0.1M KNO3 electrolyte. In the potential window in the range of -0.8-1V, at a scan rate of 25mV / s, cyclic voltammetry was scanned for 5-15 circles, and silver nanoparticles were deposited on the surface of the material to obtain nanosilver / nitrogen-doped carbon film / carbon fiber.

[0038] Figure 2 The morphology of the nitrogen-doped carbon film is obtained by coating the mesoporous material with polypyrrole and then carbonizing it. The upper end of the cut shows the original carbon fiber morphology full of grooves. The deposited carbon film is about 2 microns thick, with a relatively rough surface and granular balls. It has a large specific surface area, which is conducive to the transfer of electrons on the electrode surface.

[0039] 2. Effect of buffer pH on the electrochemical performance of phenolic substances

[0040] In order to explore the effect of pH value on the electrochemical performance of phenolic substances, the response current of nanosilver / nitrogen-doped carbon film / carbon fiber modified electrode to 200 μM hydroquinone, catechol and p-nitrophenol was studied by DPV in PBS buffer with different pH values.

[0041] The effect of pH value of buffer solution on the detection of hydroquinone, catechol and p-nitrophenol, such as Figure 3 As shown, when the pH is in the range of 5.7-8.2, the peak currents of the oxidation peaks of the three target phenolic substances all increase first and then decrease, reaching the maximum value at pH=7.2, so the buffer solution pH=7.2 is selected.

[0042] Example 4 Preparation of Nanosilver / Graphene Quantum Dots / Carbon Fiber

[0043] 1. Preparation method

[0044] The plasma-treated carbon fiber prepared in Example 1 was used as the working electrode, Ag / AgCl was used as the reference electrode, and Pt was used as the counter electrode to form a standard three-electrode system. A certain amount of graphene quantum dot aqueous dispersion solution (concentrations were 0.025mg / ml-0.2mg / ml) was added to a 0.01M PBS buffer solution at pH=7.4, and the graphene quantum dots were deposited on the surface of the material by scanning 5-15 circles by cyclic voltammetry at a potential window in the range of -2-2V and a scanning rate of 25mV / s. Silver nanoparticles were deposited by the method in Example 3, specifically: using graphene quantum dot carbon fiber as the working electrode, a certain amount of silver nitrate was added to a 0.1M KNO3 electrolyte, and the silver nanoparticles were deposited on the surface of the material by scanning 5-15 circles by cyclic voltammetry at a potential window in the range of -0.8-1V and a scanning rate of 25mV / s, respectively, to obtain nanosilver / graphene quantum dots / carbon fiber.

[0045] Figure 4 In order to modify the carbon fiber with silver nanoparticles and graphene quantum dots, there are a certain amount of silver nanoclusters on the surface of the carbon fiber grooves, which are evenly distributed on the surface of the material, greatly increasing the specific surface area and conductivity of the material.

[0046] 2. Effect of scanning rate on the electrochemical performance of hydroquinone and catechol

[0047] In order to explore the effect of scan rate on the electrode and the kinetic behavior of the target reaction on the electrode surface, 0.2 μM hydroquinone and catechol were added to 0.1M PBS buffer solution with a pH value of 7.2. The cyclic voltammetric response of nanosilver / graphene quantum dots / carbon fiber modified electrode to hydroquinone and catechol was studied by CV in the potential range of -0.2 ~ 0.6 at different scan rates (a ~ l: 25, 50, 75, 100, 125, 150, 175, 200, 225, 250, 275, 300 mV / s).

[0048] Figure 5 The effect of different scan rates on the detection of hydroquinone and catechol is shown in the figure. The scan rate range is 25~300 mV / s. As the scan rate increases, the peak current also increases and is linearly related to the square root of the scan rate. This shows that the reaction is a diffusion-controlled process.

[0049] Example 5 Preparation of Nanosilver / Carbon Film / Carbon Fiber

[0050] 1. Preparation method

[0051] The carbonized nitrogen-doped carbon film / carbon fiber prepared in Example 3 was used as the working electrode, and graphene quantum dots and silver nanoparticles were successively deposited according to the process in Example 4. Specifically, Ag / AgCl was used as the reference electrode, Pt was used as the counter electrode to form a standard three-electrode system, a certain amount of graphene quantum dot aqueous dispersion solution (concentrations were 0.025mg / ml-0.2mg / ml) was added to a 0.01M PBS buffer solution at pH=7.4, and graphene quantum dots were deposited on the surface of the material by scanning 5-15 circles by cyclic voltammetry at a potential window in the range of -2-2V and a scanning rate of 25mV / s. With graphene quantum dot carbon fiber as the working electrode, a certain amount of silver nitrate was added to a 0.1M KNO3 electrolyte, and silver nanoparticles were deposited on the surface of the material by scanning 5-15 circles by cyclic voltammetry at a potential window in the range of -0.8-1V and a scanning rate of 25mV / s, respectively, to obtain nanosilver / carbon film / carbon fiber.

[0052] 2. Explore the linear relationship of p-nitrophenol concentration

[0053] The nanosilver / carbon film / carbon fiber modified electrode was clamped with a platinum electrode clip as the working electrode and scanned 10 times by cyclic voltammetry in p-nitrophenol with a concentration of 200 μM and pH 7.2. DPV was used to detect p-nitrophenol at different concentrations (a ~ n: 1, 5, 10, 30, 70, 100, 150, 200 μM).

[0054] Figure 6 This is the DPV diagram for detecting different concentrations of p-nitrophenol in a buffer solution with pH = 7.2. As shown in the figure, the peak potential for detecting p-nitrophenol is around 0.04V. When the p-nitrophenol concentration ranges from 1 to 200 μM, the peak current increases continuously with the increase of concentration and is linearly related to the concentration. By calculation, it is found that LOD = 3s / k = 0.0073μM.

[0055] Example 6 Nanosilver / carbon film / carbon fiber electrochemical sensor for detecting dopamine, ascorbic acid and uric acid

[0056] The prepared nanosilver / carbon film / carbon fiber was used as the working electrode, Ag / AgCl as the reference electrode, and Pt as the counter electrode to form a standard three-electrode system to detect dopamine in a 0.01M PBS buffer solution at pH=7.4. The interference performance of ascorbic acid and uric acid on the detection of dopamine was investigated. The results showed that the prepared nanosilver / carbon film / carbon fiber modified electrode can simultaneously detect dopamine, ascorbic acid and uric acid.

Claims

1. Nanosilver / carbon film / carbon fiber, which is prepared by the following method: A standard three-electrode system is formed by using nitrogen-doped carbon film / carbon fiber as a working electrode, Ag / AgCl as a reference electrode, and Pt as a counter electrode. A graphene quantum dot aqueous dispersion solution is added to a 0.01M PBS buffer solution at pH=7.4, and cyclic voltammetry is performed for 5-15 cycles at a scanning rate of 25mV / s at -2-2V to deposit graphene quantum dots on the surface of the material. Using graphene quantum dot carbon fiber as a working electrode, silver nitrate is added to a 0.1M KNO3 electrolyte, and cyclic voltammetry is performed for 5-15 cycles at a potential window in the range of -0.8-1V at a scanning rate of 25mV / s to deposit silver nanoparticles on the surface of the material to prepare nanosilver / carbon film / carbon fiber. The nitrogen-doped carbon film / carbon fiber is prepared by the following method: Add 0.1M KNO3 and pyrrole monomer, take the mesoporous material coated carbon fiber as the working electrode, and prepare the polypyrrole film by electrodeposition under the conditions of 0.1g-2g pyrrole mass, 1-7V voltage range, and 30-300s time; place it in a corundum boat and carbonize it at a carbonization temperature of 400-900℃ to obtain nitrogen-doped carbon film / carbon fiber; The mesoporous material coated carbon fiber is prepared by the following method: 1) Plasma treatment of carbon fiber electrode: Tow carbon fiber is used as the base material, calcined at 400-500°C for 0.5-2h; rinsed with acetone, ethanol and deionized water for 3-5 times in sequence, and dried naturally; the treated carbon fiber is laid flat on a quartz boat, and plasma is evenly bombarded on the surface of the carbon fiber; the plasma power is 50-100W, the oxygen flow rate is 120-180ml / min, and the treatment time is 15-90s; 2) Mesoporous material coating: immerse the carbon fiber treated in step 1) in the mesoporous material for 10 to 15 hours; soak under ultrasonic action for 3 to 10 minutes, take out, and calcine for 2.5 to 3.5 hours to obtain mesoporous material coated carbon fiber.

2. The nanosilver / carbon film / carbon fiber according to claim 1, characterized in that: The mesoporous material is prepared by the following method: weigh 0.2-0.4 g P123, add 12-14 ml ethanol, 30-40 μl 1M hydrochloric acid, 1-2 ml water and 2-3 ml tetraethyl silicate, and rotate at a speed of 350-450 rpm at room temperature for 10-15 hours.

3. The nanosilver / carbon film / carbon fiber according to claim 2, characterized in that: The P123 is 0.298 g, ethanol is 12.4608 ml, 1M hydrochloric acid is 33.34 μl, H2O is 1.6848 ml and tetraethyl silicate is 2.2329 ml.

4. The nanosilver / carbon film / carbon fiber according to claim 3, characterized in that: The tow carbon fiber has 3000 carbon fibers per tow.

5. Use of the nanosilver / carbon film / carbon fiber according to claim 1 in the preparation of an electrochemical sensor; the electrochemical sensor can simultaneously detect dopamine, ascorbic acid and uric acid.

Citation Information

Patent Citations

  • Preparation method of mesoporous composite material

    CN106810194A

  • Preparation and application of nitrogen doped cotton carbon fiber modified electrode

    CN108627558A

  • Reticulated nitrogen-doped carbon-coated manganese dioxide carbon cloth electrode and preparation method and application thereof

    CN109244479A